The Socio-Political Importance of Mir Syed Ali Hamdani’ letters (Maktubat-i-Amir-e-Kabir); An Analytical Study - Ganai, Helal Ahmad; Amjad , Muhammad (Al-Amīr Research Journal for Islamic Studies, 2024)
For the guidance of common masses, religious preachers of Islam especially Sufis used to deliver Sermons (Khutbāt) but for the ruling class, they mostly prefer to send them letters in order to dissuade them from their wrong doings. The socio-political conditions of time also motivated Sufis to write letters to political elite in order to reform the social and political ethos of the Muslim community of their times. Mir Saiyid ‘Ali Hamadani popularly known in Kashmir as Amir-e-Kabir and Shah-i-Hamadan is one of the great Sufi whose collection of letters—Maktubāt-i-Amir-e-Kabir is of tremendous importance in this context. The present paper is an attempt to demonstrate the history of letter writing in the Muslim world. Further, it will critically analyze letters of Mir Saiyid ‘Ali Hamadani in order to evaluate his personality and missionary zeal. Key Words: Khutbat, Maktubat, Sultan, Socio-political Conditions, Saiyid ‘Ali Hamadani